Performance assessment of novel biomass gasification based CCHP systems integrated with syngas production. (15th January 2019) - Prakash, M.; Sarkar, A.; Sarkar, J.; Chakraborty, J.P.; Mondal, S.S.; Sahoo, R.R.
Abstract: In this study, three novel biomass gasification based tetra-generation systems for syngas, heating, cooling and power generations have been proposed and theoretically assessed for selected biomass materials. The systems, instead of using the chemical energy of the gasification products, use the thermal energy to operate both Rankine and Refrigeration cycles in three configurations, namely, steam Rankine cycle with organic Rankine Cycle and ejector refrigeration cycle (Cycle-1), binary Rankine cycle with ejector refrigeration cycle (Cycle-2) and steam Rankine cycle with combined power ejector refrigeration cycle (Cycle-3). Syngas (a mixture of hydrogen and carbon monoxide gas), which has the potential for various domestic applications, has been obtained as the gasification product. The effects of different operating parameters such as water to biomass ratio, total biomass-water mass flow rate, mass flow rate of refrigerant, generator pressure, gasification temperature and types of biomass material have been studied on the syngas and hydrogen yields, as well as coefficient of performance and overall performance index of the system. The study shows that Cycle-2 is more effective in terms of coefficient of performance and refrigeration effect whereas Cycle-1 is best for higher performance index. Hence, either Cycle-1 or Cycle-2 can be preferred depending on the requirement. Highlights: Three novel tetra-generation (syngas, heating, cooling and power) systems are proposed. Systems contain biomass gasification, steam and organic rankine cycle and ejector cycle. System performances are compared for different biomass and operating parameters.